Associations between meeting the Canadian 24-Hour Movement Guidelines for the Early Years and behavioral and emotional problems among 3-year-olds. Issue 7 (July 2019) - Carson, Valerie; Ezeugwu, Victor E.; Tamana, Sukhpreet K.; Chikuma, Joyce; Lefebvre, Diana L.; Azad, Meghan B.; Moraes, Theo J.; Subbarao, Padmaja; Becker, Allan B.; Turvey, Stuart E.; Sears, Malcolm R.; Mandhane, Piush J.
Abstract: Objectives: Primary: examine associations between meeting the 24-Hour Movement Guidelines for the Early Years and behavioral and emotional problems in a large sample of 3-year-old children. Secondary: determine the proportion of children meeting the Canadian 24-Hour Movement Guidelines. Design: Cross-sectional. Methods: Participants were 3-year olds (n = 539) from the Edmonton site of the Canadian Healthy Infant Longitudinal Development (CHILD) birth cohort. Physical activity and sleep duration were accelerometer-derived while screen time was parent-reported. Meeting the overall guidelines was defined as: (1) ≥180 min/day of total physical activity, including 60 min/day of moderate- to vigorous-intensity physical activity, (2) ≤1 h/day of screen time, and (3) 10–13 h of sleep per 24-hour period. Externalizing, internalizing, and total problem scores (lower scores representing fewer problems) were calculated from the parent-reported Child Behavior Checklist (CBCL). Descriptive statistics and linear regression models were completed. Results: Only 5% of children met the overall guidelines (all three recommendations), with 19.3%, 50.5%, and 83.1% meeting the physical activity, screen time, and sleep recommendations, respectively. Meeting more recommendations was associated with lower scores for total (B = −1.78, 95%CI: −3.03, −0.54), externalizing (B = −1.51, 95%CI: −2.80, −0.22) and internalizing (B = −1.35, 95%CI: −2.60, −0.01) problems. Similar findings were also observed for the specific combinations of: (1) physical activity and screen time and (2) sleep duration and screen time. Conclusions: Meeting more recommendations within the 24-hour Movement Guidelines was associated with fewer behavioral and emotional problems at 3-years. Few 3-year-olds met the overall guidelines. Findings support an integrated approach for healthy growth and development.